RELASI KOSAKATA FAUNA DALAM SAMPIRAN DAN ISI PANTUN â€œ1001 PANTUN PERIBAHASAâ€ KARYA SUDIADI - Novialdi, Hafiz; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe old Pantun Melayu also has a connection between sampiran and the contents of the pantun. Such relationships are like sound relationships and meaning relationships. This study discusses the interaction of sound images, interrelations of meaning images, interrelationships contained in the pantun, and interrelationships of language and matter. The interrelationship is based on the vocabulary of fauna contained in the sampun of the book